DRUG ENANTIOMERS IN CLINICAL PHARMACOLOGY - Krisna Malay, Kausalyah; D, Ezhilarasan; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The single enantiomers are considered to be safer and better alternatives to racemates, which has resulted in a need for developing single isomers as drug products. Most of the drugs in use today are chiral. It is well established that the pharmacological activity is mostly restricted to one of the enantiomers, and the individual enantiomers of racemic drugs frequently differ in their biological effects. In many cases, the inactive enantiomer shows unwanted side effects or even toxic effects. A pharmacological study reveals that there is a need for separating and quantifying enantiomers in biological samples to assess the toxic effects of such drugs. Single-enantiomer products are being re-marketed by so-called the chiral switch process. (Racemate to single enantiomer)